Gender as performance, experience, identity and, variable: A systematic review of gender research in jazz and improvisation - Canham, Nicole; Goh, Talisha; Barrett, Margaret S.; Hope, Cat; Devenish, Louise; Park, Miranda; Burke, Robert L.; Hall, Clare A. (Frontiers in Education, 2022)
There is growing interest in examining the gendered nature of music practices worldwide. Recent investigations of access to and equity in the music industry have included studies of gender discrimination in classical music, popular music, film music, and within the structure of colonisation. This paper contributes to this work by reporting the findings of a Systematic Literature Review (SLR) of research that addresses the gendered nature of jazz and improvised music practices in education settings, ensembles, and professional performance environments. Our purpose was to generate an understanding of the phenomenon of gendered jazz and improvised music practices through the following research questions: (1) what is the scope and focus of existing empirical research on gender in jazz and improvised music? (2) where has this research been undertaken, by whom, and to what purpose? (3) what methodological approaches have been employed? (4) how has gender been understood in this research? Findings indicate that research on gender in the jazz and improvisation sector is largely undertaken by women researchers working individually within the euro-anglosphere (US, UK, Australia). The majority of studies were undertaken in the qualitative paradigm with autoethnographies, case studies, ethnography, and narrative inquiry as the dominant research approaches. A small number of studies used quantitative or mixed methods with gender as the key variable. By contrast, qualitative studies focused on gendered accounts of working in the jazz and improvisation sector providing deeply personal narratives via artistic research, as illustrations of how larger institutional and societal factors shape the experiences of the individual. Given this personal focus, explicit referencing to theoretical frameworks was de-emphasised in the papers reviewed. Our discussion focuses on the individual and institutional factors that might account for these patterns of research and knowledge production as a way of framing past and present understandings of issues relating to gender in jazz and improvised music. We argue that small-scale qualitative research needs to be supported by larger-scale intersectional investigation into systemic or institutionalised phenomena that investigates how gender marginalisation is enabled through these structures. Recommendations for further research, policy and practice are provided.